2010
DOI: 10.1128/aem.02833-09
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor FarR Is Not Involved in Meningococcal Fatty Acid Resistance Mediated by the FarAB Efflux Pump and Dependent on Lipopolysaccharide Structure

Abstract: Free fatty acids are important antimicrobial substances regulating the homeostasis of colonizing bacteria on epithelial surfaces. Here, we show that meningococci express a functional farAB efflux pump, which is indispensable for fatty acid resistance. However, other than in Neisseria gonorrhoeae, the transcriptional regulator FarR is not involved in regulation of this operon in Neisseria meningitidis. We tested the susceptibility of 23 meningococcal isolates against saturated and unsaturated long-chain fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…However, no band shift was observed upon addition of purified FarR protein (data not shown). Consequently, in terms of assigning a gene to the FarR regulon, binding of FarR to the promoter region may neither be necessary nor is it sufficient as FarR binds to the farAB promoter, but clearly does not regulate expression of this transporter (Schielke et al, 2009(Schielke et al, , 2010.…”
Section: Independent Validation Of Microarray Results By Quantitativementioning
confidence: 98%
“…However, no band shift was observed upon addition of purified FarR protein (data not shown). Consequently, in terms of assigning a gene to the FarR regulon, binding of FarR to the promoter region may neither be necessary nor is it sufficient as FarR binds to the farAB promoter, but clearly does not regulate expression of this transporter (Schielke et al, 2009(Schielke et al, , 2010.…”
Section: Independent Validation Of Microarray Results By Quantitativementioning
confidence: 98%
“…This DNA-binding protein was first identified in the gonococcus (GC) and was shown to repress expression of the farAB -encoded efflux pump that is responsible for high levels of fatty acid resistance [18]. In contrast, MC FarR does not affect fatty acid resistance through FarAB, perhaps due to naturally high fatty acid resistance expressed by this pathogen [19]. Interestingly, however, MC FarR does bind to its farAB promoter region with relatively high affinity and represses farAB expression as shown by RT-PCR [20].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the expression of most genes was induced by the 4HPA molecule (type I genes), either partially (i.e., nadA) or fully (i.e., putA, gph, nmb1277) with respect to the maximal derepression achieved in the NadR mutant. Interestingly the farA transcript was also induced in MC58 by 4HPA to levels similar to those of the mutant (data not shown); however, it is likely that these subtle differences are not biologically significant, as previous reports have clearly shown that NadR (named FarR in those studies) is not involved in fatty acid resistance mediated by the FarAB efflux pump in meningococcus which exhibits high intrinsic fatty acid resistance (33,34). Intriguingly, we found that only the mafA genes (type II genes) expression responds in the opposite way to 4HPA, with mafA transcription being repressed in the presence of 4HPA and suggesting that this small molecule acts as a corepressor of NadR at the mafA1 and mafA2 promoters.…”
Section: Resultsmentioning
confidence: 75%
“…The FarR regulator was shown to bind to three binding sites overlapping and upstream of the farAB promoter and repress expression of the efflux pump (18,19). In contrast, NMB1843 has been reported to play no role in regulating fatty acid resistance in N. meningitidis, which exhibits high intrinsic fatty acid resistance (33,34). Instead, NMB1843 was demonstrated to repress expression of the meningococcal adhesin NadA (neisserial adhesin A) (23,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation